Kecernaan Bahan Kering dan Bahan Organik Jerami Padi yang Difermentasi dengan Kombinasi Kapur Tohor, Bacillus s., dan Air Kelapa pada Waktu yang Berbeda - Muhamad Amin; Muhamad Iqbal; Sofyan Damrah Hasan; Oscar Yanuarianto (Faculty of Animal Husbandry, University of Mataram, 2015)
The study aims to determine the nutrient composition, digestibility dry matter and organic matter fermented rice straw in combination with calcium carbonate, Bacillus sp., and coconut water at different times. Rice straw obtained around the city of Mataram and then was cut into pieces with 3-4 cm in size. Four treatments were applied : PI was 300 g rice straw added with a 3% solution of Bacillus sp. and 7% calcium oxide with no fermentation. Treatments 2 to 4 was similar to the first treatment but fermentation applied were for 14, 21 or 28 days respectively. The variables in the study were observed physical properties, chemical composition (dry matter, organic matter, crude protein, crude fiber, neutral detergent fiber, acid detergent fibre and lignin ) and digestibility of dry matter and organic matter of rice straw. The data obtained were analyzed using a completely randomized design with SAS statistical program package. The results showed that the fermentation time can increase the nutrient composition organic matter, crude protein, digestibility of dry matter and organic matter and decreased crude fiber (neutral detergent fibre, acid detergent fibre, hemisellulosa, cellulose and lignin) of rice straw fermented with a combination of calcium oxide, Bacillus sp, and coconut water.